Formation of musical thinking of the future teacher of music on employment on the basic musical tool (piano) (Pedagogy of Higher and Secondary Education, 2007)
The article considers stages of development of musical thinking on employment on the basic musical tool (piano), conducting principles, which underlie the forms and methods щf educational process and promote development of musical thinking of the future teacher of music.
Keywords: musical thinking; employment on the basic musical tool (piano); stages; intonation; dialogue; communication between disciplines; theoretical analysis; methods o f training; practice o f the executor